Phytosterol as functional food components and nutraceuticals - Dutta, Paresh C. (Marcel Dekker, 2011)
Responding to the magnitude of publicity currently centering on phytosterol utilization and efficacy, this reference compiles an impressive array of studies on the properties and role of phytosterols in functional food production and public health - documenting the occurrence, analysis, and biological effects of phytosterols to enhance and improve the production and development of functional food ingredients.